Improving the Retrievals of Greenhouse Gases from Ground-Based Solar Absorption Spectra - Mendonca, Joseph Sam (2017)
A quadratic speed-dependent Voigt (qSDV) line shape with line mixing (LM) has been implemented into the forward model of the spectral fitting software GFIT to improve the retrievals of total columns of CO2, CH4, and O2 from high-resolution ground-based solar absorption spectra. Absorption coefficients were calculated using the qSDV+LM spectral line shape with spectroscopic parameters for the strong 20013←00001 CO2 band centered at 4850 cm-1, the weak 30013←00001 and 30012←00001 CO2 bands centered at 6220 cm-1 and 6340 cm-1 respectively, as well as the 2ν3 band of CH4. Absorption coefficient calculations were validated using laboratory spectra of CO2 and CH4. Laboratory spectra were modeled better with the qSDV+LM when compared to using the Voigt spectral line shape. The qSDV was used to fit air-broadened, room-temperature, cavity ring-down spectra of the a^1 ∆_g←X^3 Σ_g^- O2 band. It was shown that the Voigt line shape is inadequate to model the spectral lines of this O2 band and that speed-dependent effects need to be taken into account. Spectroscopic parameters of the discrete spectral lines of the O2 a^1 ∆_g←X^3 Σ_g^- band were retrieved and implemented in GFIT. A year of ground-based solar absorption spectra acquired at Eureka (Nunavut, Canada), Park Falls (Wisconsin, USA), Lamont (Oklahoma, USA), and Darwin (Northern Territory, Australia) were processed using GFIT. Total columns of CO2, CH4, and O2 were retrieved using absorption coefficients calculated assuming a Voigt spectral line shape and the qSDV+LM (with LM used when applicable). With the qSDV+LM, spectral fits of CO2 and CH4 improved as a function of solar zenith angle. The airmass dependence of the retrieved columns of CO2, CH4, and O2, as well as the column-averaged dry-air mole-fraction of CO2 (XCO2) decreased while the accuracy of XCO2 improved. Ph.D.